Pengaruh Efektivitas Kepemimpinan Kepala Sekolah dan Lingkungan Kerja Terhadap Prestasi Kerja Guru SMA Negeri di Kota Samarinda - Poernomo, Soerjo Adi; Hanim, Zaenab; Komariyah, Laili (CV. Creative Tugu Pena, 2022)
The purpose of this study was to determine the effect of (1) the effectiveness of the principal's leadership on teacher work performance, (2) the work environment on teacher performance, (3) the effectiveness of the principal's leadership and the work environment together on teacher work performance. This type of research uses a correlational method with a quantitative approach, including validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The research sample was 100 teachers in 5 public high schools in the city of Samarinda which were selected by a simple random sampling technique. Based on the results of the study, it shows that (1) there is a significant influence between the effectiveness of the principal's leadership on teacher work performance by 31.20% (2) there is a significant influence on the work environment on teacher work performance by 30.70%, (3) there is a jointly significant influence between the effectiveness of the principal's leadership and the work environment on the teacher's work performance is 31.60%. The implication of this research is that teachers will have high work performance, if the leader provides effective leadership to the school he leads, in addition to improving the work performance of the principal by paying attention to the teacher's work environment. Keywords: Leadership Effectiveness, Work Environment, Work Achievement